SIGS-S: A Web Application and a Mobile Application for Social and Health Care Data Management - Fernandes, Eduardo; Silva, Marcio Aparecido; Cagnin, Maria Istela (Histórico da iSys - Brazilian Journal of Information Systems (SERVIDOR ANTIGO - UNIRIO), 2016)
In Brazil, information systems have been used to support government activities, such as public social and health care. For instance, SIGS is a web information system for management of social programs. Another example of information system is e-SUS for health care data management. Considering that crossing data from social and health care may be useful in decision-making for both areas, the SIGS-S project was proposed. It consists of a web appli- cation and a mobile application for social and health care data management. SIGS-S Web is a web application composed by two subsystems, SIGS-S Web So- cial, resulting of the reengineering of SIGS, and SIGS-S Web Saúde, inspired by data forms from e-SUS. SIGS-S Mobile Saúde is a mobile application to support health data collection. Processes ProFap and ProFap-R were used during their development. As a result, both web and mobile applications, as well as web services to support cross-application data exchange, were developed. Further- more, it was prepared the documentation for both applications to help future software maintenance. Both applications were developed and validated with participation of stakeholders (health users and government managers).